Six New neo-Clerodane Diterpenoids from Aerial Parts of Scutellaria barbata and Their Cytotoxic Activities - Yang, Guo-Chun; Hu, Jia-Hui; Li, Bing-Long; Liu, Huan; Wang, Jia-Yue; Sun, Li-Xin (Planta Medica, 2018)
Six new neo-clerodane diterpenoids (1–6), scutebatas X – Z, A1-C1, along with twelve known ones (7–18) were obtained via the phytochemical investigation of the aerial parts of Scutellaria barbata. Their structures were established by detailed spectroscopic analysis. The absolute configurations of 1 and 2, as the representative members of this type, were identified based on a circular dichroic exciton chirality method. Moreover, in vitro cytotoxicity of compounds 1–6 were evaluated against three human cancer cell lines (SGC-7901, MCF-7, and A-549) using the MTT method. Compound 6 showed cytotoxic activities against all the three cell lines with IC50 values of 17.9, 29.9, and 35.7 µM, respectively.
Keywords: neo-clerodane diterpenoid; Scutellaria barbata; Lamiaceae; absolute configuration; cytotoxicity